ANALISIS PERSEPSI WARGA MUHAMMADIYAH PADA KONSEP IMAN KEPADA ALLAH DAN APLIKASINYA DALAM KEHIDUPAN SEHARI-HARI - Nurul Yaqin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
The focus of this research is to analyze the concept of faith in Allah in HPT as the basis for the perception of Muhammadiyah residents in Sugihan-Solokuro-Lamongan village on the concept of Faith in Allah and its application in daily life. This research use desciptive qualitative approach. The informants of this research were the head of the branch, the head of the da'wah section, and two members of Muahammadiyah Sugihan. Data was collected using interview, observation, documentation and literature study techniques. The results of the study show that the perception of Muhammadiyah residents Sugihan on the concept of Faith in God follows HPT, namely that Allah is the only Rabb; creator, sustainer and ruler of this universe. He is al-Ihah al-Haq who has the right to be worshiped, there is no true worship except Him. He has a name and character as stated in the Qur'an and al-Hadith al- maqbullah. Determination of the name and nature of Allah based on the Qur'an and al- hadith, without ta'wil / tahrif and tafwidh and without asking the question